Brain and spinal cavernous malformations - Anastasia Gotko; Juri Kivelev; Anatoliy Son (Ukrainian Neurosurgical Journal, 2013)
The literature review on brain and spinal cavernous malformation is given. The variants of disease clinical manifestation, genetics and pathophysiology of caverns are considered. Modern methods of diagnostics are given and also the risk of hemorrhage, treatment policy, determined by the patient’s condition, process localization, type of clinical course, hemorrhage severity, the degree of volume effect.